Soil resistance to penetration in integrated crop-livestock with grazing intensities and fertilization - Bratti, Felipe; Locatelli , Jorge Luiz; Ribeiro, Ricardo Henrique; Romani de Mello, Guilherme; Renan Besen, Marcos; Thiago Piva, Jonatas (Scientia Agraria Paranaensis, 2021)
Soil compaction periodic monitoring through soil penetration resistance (PR) has been a rapid, easy, and economic way to evaluate the different management systems on soil physical attributes effect. The aim was to evaluate the grazing intensities and nitrogen fertilization effect in two winter/summer seasons (black oat/corn/black oat/soybean) on soil PR in an integrated crop-livestock system. The experimental design was in randomized blocks, in a factorial 2×3 [2 black oat pasture residual heights (15 and 7 cm), under rotational grazing × 3 nitrogen rates applied to pasture (0, 75 and 150 kg N ha-1)], with 4 repetitions. Soil PR was measured using an electronic penetrograph to an 80 cm depth. Soil samples were collected to determine gravimetric moisture. In the first year, 75 kg N ha-1 resulted in the highest depth compaction while intensive grazing (7 cm) resulted in the highest PR. In the second year, plots without N resulted in lower PR levels, mainly in the superficial layers. However, the rate of 150 kg N ha-1 presented greater compaction in the 15-20 cm layer after grazing. The high moisture levels in depth reduced PR in all evaluated periods, highlighting the close relationship between both variables. General grazing heights did not affect PR, but the use of systems that increase residues production, as moderate grazing and nitrogen fertilization might be an alternative to mitigate the soil compaction in surface layers effects.